2000
DOI: 10.1080/09515070010027607
|View full text |Cite
|
Sign up to set email alerts
|

'Psychodynamic and Religious?' Religiously committed psychodynamic counsellors, in training and practice

Abstract: This article supports a case for an increased research focus upon and within counsellor training with consideration of the counsellor's religious orientation. This aspect of professional diversity was investigated via in-depth interviews with eight religiously-committed psychodynamic counsellors. Their accounts of experiences in training, supervision, personal therapy and professional practice were subjected to qualitative analysis using grounded theory methods. Three major themes were identi ed: changes occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…While most studies concentrate on stress in qualified professionals, trainees in such professions may be even more vulnerable (Halewood & Tribe, 2003;Truell, 2001). Stressors are highly likely to be exacerbated in training, both generally (e.g., Jensen, 1995), and with respect to specific diversities (e.g., Martinez & Baker, 2000). Millon et al (1986) have suggested that training in psychology as a career is "full of intrinsic stressors", presenting "student practitioners with multiple academic and clinical demands which often lead to early self doubt" (p. 242).…”
Section: Introductionmentioning
confidence: 99%
“…While most studies concentrate on stress in qualified professionals, trainees in such professions may be even more vulnerable (Halewood & Tribe, 2003;Truell, 2001). Stressors are highly likely to be exacerbated in training, both generally (e.g., Jensen, 1995), and with respect to specific diversities (e.g., Martinez & Baker, 2000). Millon et al (1986) have suggested that training in psychology as a career is "full of intrinsic stressors", presenting "student practitioners with multiple academic and clinical demands which often lead to early self doubt" (p. 242).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the counseling profession's historical aversion to incorporating religious ideas into therapy, some counselors may do their best work when they refuse to compartmentalize their religious faith in session. Martinez and Baker () found that certain counselors access considerable energy by drawing on their own faith during treatment. Martinez and Baker's qualitative study revealed that their eight participants, all religious counselors in the United Kingdom, felt compelled by God to enter the profession.…”
Section: Diversity Religious Mismatch and Counselor Self‐disclosurementioning
confidence: 99%
“…Most of Martinez and Baker's () participants expressed the concern that counselors' religious self‐disclosure to clients could evoke strong, distracting transference. In contrast, one participant stated her belief that religious self‐disclosure was analogous to informing clients about one's counseling credentials and theoretical approach (Martinez & Baker, ). Another participant contended that a counselor who unconditionally refused to engage in religious self‐disclosure might do a disservice to clients who shared similar beliefs and sought understanding.…”
Section: Diversity Religious Mismatch and Counselor Self‐disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…What made the task even more of a challenge was the fact that, as acknowledged by writers in the UK (Martinez & Baker, 2000;Swinton, 2007) and in the USA (Richards & Bergin, 1997;Brawer et al, 2002;Schulte et al, 2002;Aten & Hernandez, 2004;Cassidy, 2007;Delaney et al, 2007;Young et al, 2007;Post & Wade, 2009) an approach developed by Crabb in the USA (Crabb, 1987;Kallmier, 2011:7) and, as already explained, it was used as the foundation for Waverley's existing (unvalidated) certificate/diploma in counselling. While over the years I had become familiar with the approach, I was aware that the definition and practice of the model would need to be significantly adapted if it was to be deemed appropriate for use in a professional counselling programme validated by a university.…”
Section: Introduction and Personal Backgroundmentioning
confidence: 99%